SISTEM INFORMASI SIMPAN PINJAM CU. HARMONI MEDAN - Hutagalung, Johanna Kezia; Hutapea, Marlyna Infryanty; Purba, Dimita H. P. (Universitas Methodist Indonesia, 2023)
CU. Harmoni is engaged in capital formation business through deposits or savings from members. Benefits of the establishment of CU. Harmony is to help members based on the principle of kinship. Number of CU members. Harmoni as a shareholder is 805 people and for education savings members is 227 people. With the number of existing members, the cooperative management still conducts savings and loans transactions using manual systems such as recording into books and using Microsoft Excel. This can be seen from the cooperative management carrying out data processing services for member transactions, deposits, loans, installments, and as well as preparing reports.A lot of data will be processed, so there will be errors in recording and calculations resulting in errors in compiling a report. The author proposes a problem-solving system in the form of building a computerized storage system for member savings and loans and installment payment collection data stored in a database. The system to be built is a data input system for borrowing and paying members using a VB NET 2010-based application program with a MYSQL database The system to be built can help CU administrators.